Design of a balance training machine for rehabilitation of stroke patient - Lim, Chee Siong. (2013)
This project aims to design and implement a machine that delivers a reliable balance training machine that is capable of assisting stoke patients who suffers from muscular recovery to improve their ability to balance. The machine is to provide sudden perturbation and rocking motions to simulate the effects similar to sudden braking and acceleration of transportation units and the situation of slippage. Since perturbations and acceleration is concerned, it is imperative to realize the importance of the kinematic and dynamic characteristics of the system. Hence a critical and substantial portion was dedicated to analyze them.